Fractures of the proximal femur in the elderly in a sub-Saharan country - Mebouinz, Ferdinand N.; Diouf, Joseph D.; Sane, Jean C.; Diao, Souleymane; Kasse, Amadou; S., Mouhammadou Habib (International Journal of Research in Orthopaedics, 2020)
Background: The aim of this study was to describe the epidemiological, radiographic and therapeutic profile of the fractures of the proximal femur in the elderly in a sub-Saharan country. Methods: A retrospective longitudinal study was carried out at the orthopedic trauma department of Idrissa Pouye Hospital in Senegal. Sixty-six patients recruited were aged at least 90 years; and treated for proximal femur fracture between 2008 and 2017. Results: The median age of the patients was 91 years (90-107). Females represented 54.5%. The fracture was located in the right 65.2%. Femoral neck fractures were 53% predominant with 94.3% type IV according to Garden’s classification. Concerning the 31 patients with a pertrochanteric fractures, 61.3% were stable and 38.7% unstable. The time taken for seeking hospital care was an average of 5.8±9.7 days. All patients had a preoperative anesthesic score less than 4 according to the American society of anesthesiologists (ASA). The therapeutic indication was functional in 15.1% of cases, surgical by internal fixation in 39.2% and by arthroplasty in 45.7% of cases. Pertrochanteric fractures were managed by a dynamic hip screw (DHS) in 68.2% and by gamma nail in 18.2%. Femoral neck fractures were managed by Moore’s arthroplasty in 93.3% and by bipolar hip prothesis (BHP) in 6.7%. Conclusions: Fractures of the proximal femur represent a growing problem in sub-Saharan Africa. For patients above 90 years, the management remains essentially surgical by internal fixation in pertrochanteric fractures or by arthroplasty in cervical fractures.